2020
DOI: 10.1186/s40168-020-00822-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of phages on soil bacterial communities and nitrogen availability under different assembly scenarios

Abstract: Background: Bacteriophages, the viruses infecting bacteria, are biological entities that can control their host populations. The ecological relevance of phages for microbial systems has been widely explored in aquatic environments, but the current understanding of the role of phages in terrestrial ecosystems remains limited. Here, our objective was to quantify the extent to which phages drive the assembly and functioning of soil bacterial communities. We performed a reciprocal transplant experiment using natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 83 publications
(89 reference statements)
4
90
0
Order By: Relevance
“…The influence of ecological niches on the evolutionary divergence of viruses was demonstrated earlier for T4-related phages (distinguished in the literature as a superfamily), Far-T4-related phages and other bacterial viruses – on the basis of data obtained from metagenomes, metaviromes and phage genomes from various sources ( Desplats and Krisch, 2003 ; Filée et al, 2005 ; Bellas and Anesio, 2013 ; Roux et al, 2015 ; Braga et al, 2020 ). However, for some phages, the isolation-related features of their ecological niches are not the only factors that can drive evolutionary divergence in the phage groups.…”
Section: Discussionmentioning
confidence: 74%
“…The influence of ecological niches on the evolutionary divergence of viruses was demonstrated earlier for T4-related phages (distinguished in the literature as a superfamily), Far-T4-related phages and other bacterial viruses – on the basis of data obtained from metagenomes, metaviromes and phage genomes from various sources ( Desplats and Krisch, 2003 ; Filée et al, 2005 ; Bellas and Anesio, 2013 ; Roux et al, 2015 ; Braga et al, 2020 ). However, for some phages, the isolation-related features of their ecological niches are not the only factors that can drive evolutionary divergence in the phage groups.…”
Section: Discussionmentioning
confidence: 74%
“…Accordingly, it has been proposed that terrestrial viruses also play major roles in their respective ecosystems (Kuzyakov and Mason‐Jones, 2018; Pratama et al ., 2020). Recent research revealed that soil viruses can infect key carbon cyclers (Emerson et al ., 2018; Trubl et al ., 2018), encode AMGs associated with biomass degradation (Emerson et al ., 2018; Trubl et al ., 2018; Jin et al ., 2019) and impact nitrogen availability in soil (Braga et al ., 2020). However, the low prevalence of viral sequences in metagenomes and the lack of universal marker genes have hampered the understanding of the diversity and the roles of viruses in the environment particularly in soil ecosystems compared with marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…To expand our knowledge on soil viruses and their putative contributions to soil microbial processes, we performed a shotgun metagenomic analysis of virus‐enriched soil microbiomes using tangential flow filtration (TFF) system of two French agricultural soil suspensions. Using a dataset that was obtained in a previous study (Braga et al ., 2020) we refined the quality of the viral genomes and conducted a customized taxonomic and host prediction analysis, followed by functional annotation of genes and mining of AMGs (see Supplementary Information). Briefly, soil samples from two INRA experimental farms (Dijon and Montpellier) were sieved (4 mm), homogenized and stored at −20 °C prior to downstream procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Soils hold an enormous viral reservoir, but we know remarkably little about their diversity, activity, host interactions, lysis-induced C-cycling, and persistence as compared to other environments [18, 19]. Viruses can affect soil C cycling by stopping microbial metabolism during lytic infections and releasing cell-derived nutrients into the environment [20]. These nutrients can either fuel other organisms’ metabolism or be stabilized via entombing effects [21].…”
Section: Introductionmentioning
confidence: 99%